Visions of the future in the ‘new’ Swahili novel: Hope in desperation? - Mikhail Gromov (Tydskrif vir Letterkunde, 2017)
The ‘new’ novel in Swahili, the most significant phenomenon in Swahili literature in the recent decades, has dealt with the questions of the future of the African continent and the world as one of its central themes. Kenyan and Tanzanian authors, whose novels are analysed in the article, present in their works a rather gloomy, apocalyptic-type visions of the future of humanity - but at the same time, leave the readers with hope that the catastrophic situations described in their books may be prevented or solved by joint effort of all the people of Africa joined into one nation.